Research on the Influencing Factors of the Entrepreneurial Intention of People Returning from Urban to Rural Areas: The Views of New Development Concept - Yao Zuchan; Lian Zhihua (SHS Web of Conferences, 2022)
This paper focuses on the entrepreneurial intention for “people returning from urban to rural areas “, the research selects three towns with different economic levels in Liancheng County of Fujian Province of China. Through field visits, in-depth interviews and questionnaires, it deeply explores the reasons, experiences, difficulties and contributions to rural construction of “ people returning from urban to rural areas “, and systematically understands the new demographic dividend caused by “ people returning from urban to rural areas “ in combination with the local policy environment and the present situation of entrepreneurship. Using simple random sampling and scientific econometric methods, this paper makes an empirical analysis of 532 samples of “ people returning from urban to rural areas “, and finally concludes that “ people returning from urban to rural areas “ to start a business can give birth to five new demographic dividends, such as demographic labor dividend, demographic quality dividend, demographic consumption dividend, policy dividend and social harmony dividend. In addition, this study constructs a theoretical model of “returning to the city” and finds that the policy environment, individual capital and personal motivation of people returning from urban to rural areas have significant influences on the entrepreneurial intention.